2008
DOI: 10.1590/s1135-57272008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre el grado de control de la hipertensión arterial, la comorbilidad y los costes en personas de más de 30 años durante el año 2006

Abstract: Those individuals whose arterial hypertension was poorly controlled displayed a greater burden of morbidity and a similar healthcare cost in comparison to those under good control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…This is consistent with another study which showed that the support of a family member in patient's adherence behaviours, together with educational measures, can be effective in improving adherence (Pladevall et al 2010). As suggested by Sicras-Mainar et al (2008), adequate adherence to treatment can improve blood pressure control and, indirectly, help in reducing the burden of this public health problem. Morbidity, mortality and healthcare expenditure, as uncontrolled hypertension, either with or without CV event, may lead to increased clinic visits, emergency room visits and/or hospital admissions.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is consistent with another study which showed that the support of a family member in patient's adherence behaviours, together with educational measures, can be effective in improving adherence (Pladevall et al 2010). As suggested by Sicras-Mainar et al (2008), adequate adherence to treatment can improve blood pressure control and, indirectly, help in reducing the burden of this public health problem. Morbidity, mortality and healthcare expenditure, as uncontrolled hypertension, either with or without CV event, may lead to increased clinic visits, emergency room visits and/or hospital admissions.…”
Section: Discussionsupporting
confidence: 87%
“…As suggested by Sicras‐Mainar et al . (), adequate adherence to treatment can improve blood pressure control and, indirectly, help in reducing the burden of this public health problem. Morbidity, mortality and healthcare expenditure, as uncontrolled hypertension, either with or without CV event, may lead to increased clinic visits, emergency room visits and/or hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The chief objective of the treatment and control of HBP is to reduce cardiovascular morbimortality associated with HBP. 16 17 …”
Section: Introductionmentioning
confidence: 99%